2015
DOI: 10.14348/molcells.2015.0125
|View full text |Cite
|
Sign up to set email alerts
|

NMAAP1 Expressed in BCG-Activated Macrophage Promotes M1 Macrophage Polarization

Abstract: Macrophages are divided into two subpopulations: classically activated macrophages (M1) and alternatively activated macrophages (M2). BCG (Bacilli Calmette-Guérin) activates disabled naïve macrophages to M1 macrophages, which act as inflammatory, microbicidal and tumoricidal cells through cell-cell contact and/or the release of soluble factors. Various transcription factors and signaling pathways are involved in the regulation of macrophage activation and polarization. We discovered that BCG-activated macropha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 47 publications
0
7
1
Order By: Relevance
“…Generally, Arg1 , Nos2 and CD163 together represent an immunosuppressive environment but BCG treatment only impacted Arg1 expression. This is in contrast to the study by Liu et al who found that Arg1 expression was not modulated in RAW macrophages when stimulated with BCG Shanghai [ 50 ]. Thus, Arg1 modulation may be a strain specific effect or an effect that is only observed in vivo.…”
Section: Discussioncontrasting
confidence: 99%
“…Generally, Arg1 , Nos2 and CD163 together represent an immunosuppressive environment but BCG treatment only impacted Arg1 expression. This is in contrast to the study by Liu et al who found that Arg1 expression was not modulated in RAW macrophages when stimulated with BCG Shanghai [ 50 ]. Thus, Arg1 modulation may be a strain specific effect or an effect that is only observed in vivo.…”
Section: Discussioncontrasting
confidence: 99%
“…These studies highlight the complexity and importance of these cells in response to infection and inflammation (55,57), but also reveal their role in immune homeostasis (1,2,58,59). Peritoneal macrophages follow similar activation pathways to other macrophage lineages, where M1 macrophages activated by IFNg and TNFa have enhanced microbicidal or tumoricidal capacity and secrete high levels of pro-inflammatory cytokines and mediators (60), while IL-4 activated M2 macrophages reduce inflammation and contribute to tissue repair through secretion of IL-10 and TGF-b (61,62). Although M2 macrophages have antiinflammatory roles, dysregulation of these signaling pathways also induce inflammation and immunopathology (38), which we investigated using the in vivo model of IL-4c induced peritonitis.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages are often classified as the classically activated M1 type and alternatively activated M2 type based on cell functions. M1 macrophages are primarily stimulated by lipopolysaccharide (LPS) or IFN-γ ( 16 ) and possess high antigen-presenting capabilities ( 17 ), which are characterized by the high secretion of pro-inflammatory cytokines, such as IL-6, IL-12, IL-23 and TNF-α ( 18 ), to promote a Th1 response, and microbicidal and tumoricidal activities ( 19 ). M2 macrophages are polarized via IL-4, IL-10, and IL-13 and exhibit a weak antigen-presenting ability ( 20 ).…”
Section: Introductionmentioning
confidence: 99%